RENDEMEN DAN KOMPOSISI PROKSIMAT GELATIN KULIT IKAN BELUT DAN LELE PADA KEADAAN SEGAR DAN KERING - Hafni Rahmawati; Yudi Pranoto (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
Skin of swam ell and catfish were potential to gelatin extracted. Swamp ell skin doesn’t have scales, with much mucus and a few fat for catfish, it’s different from another fish skin that gelatin extracted usually. This research was studied yield and proximate gelatin extracted from skin of swam ell and catfish. Influence of drying was observed too.The first stage of the research was raw material preparation (fresh and dryfish skin) soaked in aquadest for 4 hours. Fish skin extracted using 0,05 M aceticacid for 10 hours, washed in water and then extracted using aquadest at 80oC for 2 hours to get gelatin liquid, the liquid was filtrated. Filtrat was dried in cabinet dryerat 55oC for 48 hours to get gelatin layers, and then blended to get gelatin granule.The results were gelatin yield from dry fish skin lower than fresh fish skin. Gelatin protein from dry fish skin more higher than fresh skin. Influence of fish skin drying was decrease gelatin ash and fat, but gelatin moisture wasn’t influenced. Gelatin from fresh skin swamp ell was the best gelatin with moisture 9,91%, ash 3,07%,protein 91,61%, lipid 0,82%.